PENGARUH KEKUATAN TARIK DAN KEKUATAN BENDING KOMPOSIT HYBRID DAN NON-HYBRID MENGGUNAKAN METODE VACUUM BAGGING - Hazhari, Fadhlah; Sehono, Sehono; Setiawan, Ferry (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2022)
Developments in the field of materials, especially the use of polymers as basic materials, are growing, this is because it meets human needs in improving welfare by processing a basic material into a material that can be used. Synthetic materials such as polymers are widely used in the manufacture of materials combined with other materials. So that it can create new materials either by adding natural fibers or synthetic fibers. Composites can be arranged using natural fibers, such as jute fibers then combined with woven roving. Jute fiber is an organic waste that is widely obtained as a burlap sack hole in traditional markets. Synthetic fibers or artificial fibers have advantages such as strong, corrosion and heat resistant fibers and are easy to mass produce. Making composites can be done several methods, one of which is using the vacuum bagging method with a technique of using pressure to direct the resin to the fibers. The researcher's goal is to determine the characteristics of tensile tests and bending tests using vaccum bagging. There are also tests carried out in the form of tensile tests that refer to the ASTM D638 standard variations of natural and synthetic fiber specimens (hybrid) In the form of yield values of 62.94 Mpa and tensil 85.9. Non-hybrid fibers can be yielded at 28.7 Mpa and tensile at 32.9 Mpa. While the bending test. In hybrid fibers, bending strength is obtained with a value of 1,126.96 MPa. In non-hybrid fibers, bending strength results were obtained with a value of 643.30 Mpa.